1978
DOI: 10.1136/adc.53.12.939
|View full text |Cite
|
Sign up to set email alerts
|

Improved accuracy of lactose tolerance test in children, using expired H2 measurement.

Abstract: SUMMARY Expired hydrogen and blood glucose were measured during an oral lactose tolerance test in 163 children aged between 9 months and 14 years. Lactose malabsorption, defined as an abnormal increase in expired H2 during a lactose tolerance test, was found in 54 children. Of these, 30 were found to be lactose intolerant as the increased expired H2 was accompanied by clinical symptoms. The other 109 children, in whom there was no rise in expired H2, were assumed to have normal lactose absorption. In children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

1983
1983
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 10 publications
1
15
0
2
Order By: Relevance
“…The diagnosis of lactose malabsorption is based on a combination of clinical fi ndings and the results of appropriate tests (11, [15][16][17][18][19]. The use of screening tests for lactose malabsorption in the diagnosis of lactose intolerance has received wide attention (11).…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis of lactose malabsorption is based on a combination of clinical fi ndings and the results of appropriate tests (11, [15][16][17][18][19]. The use of screening tests for lactose malabsorption in the diagnosis of lactose intolerance has received wide attention (11).…”
Section: Diagnosismentioning
confidence: 99%
“…In adults, it has a sensitivity of 75% and a specifi city of 96%. However, in children it is cumbersome, invasive, and time con suming and has largely been replaced by the lactose breath hydrogen test (17,19). Although this latter test really measures lactose nonabsorption rather than lactose hydrolysis and monosaccharide uptake, its sensitivity (100%) and specificity (100%) (II) are supcrior to those for the lactose absorption test, and it is simple and noninvasive (II, [15][16][17][18][19][20].…”
Section: Lactose Absorption Test and Lactose Breath Hydrogen Testmentioning
confidence: 99%
“…Currently used methods for the diagnosis of lactose intolerance include the breath hydrogen test (BHT), estimation of lactase enzyme from an intestinal biopsy and the lactose tolerance test. In this study, the BHT was used because it is easy to perform and is fairly dependable [13]. However, there still exists controversy in its interpretation, the amount of the substrate used for challenge and the magnitude of the hydrogen level in the breath to be taken as positive result [14].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that in some instances colonic bacteria can consume hydrogen [41,42] to produce methane [24], Sleeping [43] and smoking [44,45] will increase the rise in hydrogen not related to lactose. The prior use of antibiotics may increase or decrease the rise in hydrogen, depending on the anti biotic used [42,46], In hypolactasia, an increment in exhaled hydrogen concentra tion of > 20 ppm or > 0.3 ml/min over the baseline is seen [28,30], Some investigators suggest a cutoff point of 10 ppm, especially in children [47,48]. A lower cutoff point should also be used, when whole milk or lower physiologic doses of lactose are used.…”
Section: Diagnostic Methodsmentioning
confidence: 99%